2011
DOI: 10.1097/jom.0b013e318221c6de
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Habits, Alertness, Cortisol Levels, and Cardiac Autonomic Activity in Short-Distance Bus Drivers

Abstract: The differences found between morning and afternoon shifts point out to the need of the implementation of educational strategies to compensate the sleep loss associated with an early work schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 40 publications
(38 reference statements)
1
25
1
Order By: Relevance
“…A PSQI score greater than 4 points is defined as “poor sleep quality.” The ESS measures daytime sleepiness. An ESS score greater than 10 represents “excessive daytime sleepiness” (Diez et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…A PSQI score greater than 4 points is defined as “poor sleep quality.” The ESS measures daytime sleepiness. An ESS score greater than 10 represents “excessive daytime sleepiness” (Diez et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Edwards et al (2001) reported that earlier waking was followed by prolonged elevation of cortisol for several hours. A recent study comparing waking and evening cortisol samples in two groups of bus drivers suggested that there was less decline over the day in early shift workers than afternoon shift workers, but the samples were not timed in relation to waking (Diez et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the methods used in this real-life setting were simple and can be used both in interventional studies and in follow-up studies. In occupational studies, using actigraphy may give a better estimate of the length of sleep than does a subjective estimation alone [35, 36]. …”
Section: Discussionmentioning
confidence: 99%